Implementasi Doktrin Kristus (Kristologi) Dalam Pendidikan Agama Kristen - Oktapiani , Maya; ., Nanda; S, Olivia Diana Sofa.; Desmita , Jessy; Sarmauli , Sarmauli (CV. ITTC INDONESIA, 2024)
This article examines the implementation of the doctrine of Christ (christology) in the context of contemporary Christian religious education. Through a comprehensive analysis of current literature and pedagogical perspectives, this research explores the challenges and strategies in integrating Christological understanding into the Christian religious education curriculum. Using a qualitative approach and content analysis, this article identifies three main areas: 1) the theological foundations for Christology-based education, 2) contemporary challenges in the implementation of Christ's doctrine, and 3) pedagogical strategies for effective integration. The research results show that effective implementation of Christology requires a balance between doctrinal fidelity and contextual relevance, supported by a transformative learning methodology.